A cluster-randomized crossover trial of Montessori activities delivered by family carers to nursing home residents with behavioral and psychological symptoms of dementia. (March 2020) - Mbakile-Mahlanza, Lingani; van der Ploeg, Eva S.; Busija, Lucy; Camp, Cameron; Walker, Helen; O'Connor, Daniel W.
ABSTRACT: Objectives: One-on-one structured Montessori-based activities conducted with people with dementia can improve agitation and enhance engagement. These activities may however not always be implemented by nursing home staff. Family members may present an untapped resource for enabling these activities. This study aimed to evaluate the impact of the Montessori activities implemented by family members on visitation experiences with people who have dementia. Design: Cluster-randomized crossover design. Setting: General and psychogeriatric nursing homes in the state of Victoria, Australia. Participants: Forty participants (20 residents and 20 carers) were recruited. Intervention: During visits, family members interacted with their relative either through engaging in Montessori-based activities or reading a newspaper (the control condition) for four 30-minute sessions over 2 weeks. Measurements: Residents' predominant affect and engagement were rated for each 30-second interval using the Philadelphia Geriatric Center Affect Rating Scale and the Menorah Park Engagement Scale. The Pearlin Mastery Scale was used to rate carers satisfaction with visits. The 15-item Mutuality Scale measured the carers quality of their relationship with the resident. Carers' mood and overall quality of life were measured using the Center for Epidemiological Studies Depression Scale and Carer-QoL questionnaires, respectively. Results: Linear regressions within the generalized estimating equations approach assessed residents' and carers' outcomes. Relative to the control condition, the Montessori condition resulted in more positive engagement ( b = 13.0, 95%CI 6.3–19.7, p < 0.001) and affect ( b = 0.4, 95%CI 0.2–0.6, p < 0.001) for the residents and higher satisfaction with visits for carers ( b = 1.7, 95%CI 0.45–3.00, p = 0.008). No correction was applied to p -values for multiple comparisons. Conclusion: This study strengthens the evidence base for the use of the Montessori programs in increasing well-being in nursing home residents. The findings also provide evidence that family members are an additional valuable resource in implementing structured activities such as the Montessori program with residents.